Tessier No. 3 and No. 4 clefts: Sequential treatment in infancy by pre-surgical orthopedic skeletal contraction, comprehensive reconstruction, and novel surgical lengthening of the ala base-canthal distance. Issue 7 (September 2015) - Spolyar, John L.; Hnatiuk, Mark; Shaheen, Kenneth W.; Mertz, Jennifer K.; Handler, Lawrence F.; Jarial, Ravinder; Camilo Roldán, J.
Abstract Background Repair of facial clefts implies wide tissue mobilization with multi-stage surgical treatment. Authors propose pre-surgical orthopedic correction for naso-oro-ocular clefts and a novel surgical option for Tessier No. 3 cleft. Methods Two male infants, a Tessier No. 3 cleft (age 7 months) and another Tessier No. 4 (age 3months), were treated with a modified orthopedic Latham device with additional septo-premaxillary molding and observed to age four years. Tessier No. 3 orthopedic measurements were obtained by image corrected cephalometric analysis. Subsequent repair included tissue expansion on Tessier No. 4 and naso-frontal Rieger flap combined with myocutaneous upper lid flap on Tessier No. 3. Results Orthopedic movements ranged from 18.5 mm in bi-planar to 33 mm in oblique analyses. Tissue margins became aligned with platform normalization. Tissue expansion on Tessier No. 4 improved distances from ala base-lower lid and subalar base-lip. The naso-frontal flap combined with myocutaneous upper lid flap on Tessier No. 3 had similar achievement, but also sufficiently lengthened ala base-canthal distance. Conclusions Repairs were facilitated by pre-surgical orthopedic correction. The naso-frontal flap combined with an upper lid myocutaneous flap seems viable as a single-stage option to lengthen ala base-canthal distance to advance repair achievement in unilateral Tessier No. 3.